Nivel de estrés laboral en docentes de educación primaria de la Institución Educativa Rosa Agustina Donayre de Morey, distrito de Iquitos 2022 - Linares Capillo, Luz Esmith (2023)
The objective of this research was to determine the level of work stress in elementary school teachers of the "Rosa Agustina Donayre de Morey" Educational Institution during the year 2022. The type of study is non-experimental with a descriptive design, with a population of 40 teachers and a sample of the total population, using non-probabilistic sampling. The survey technique was used and the ED-6 Stress Scale survey questionnaire was used as an instrument, being structured for each variable with its respective dimension and item; likewise, they were validated by three research professors of the University and to obtain the reliability the Cronbach's alpha statistic was used, which indicates that they are reliable. Statistical graphs were used to analyze the tables of data percentages and averages. The most relevant conclusions were the following: The level of work stress in primary education teachers of the "Rosa Agustina Donayre de Morey" Educational Institution during the year 2022 is normal (Table 8 and Graph 7). The dimension with moderate level is Demotivation with 60% and the dimension with the highest level is Pressures, with 75%. The data collected were evaluated by means of statistical tables and graphs, which made it possible to describe the variable.